A pigeon paramyxovirus type 1 isolated from racing pigeon as an inactivated vaccine candidate provides effective protection - Yajie Zhang; Weifan Wang; Yongkun Li; Jinming Liu; Wenbin Wang; Jun Bai; Zengqi Yang; Haijin Liu; Sa Xiao (Poultry Science, 2022)
ABSTRACT: Pigeon paramyxovirus type 1 (PPMV-1), a variant of Newcastle disease virus (NDV), causes severe Newcastle disease (ND) in pigeons. However, there is no PPMV-1 vaccine available worldwide. In this study, a strain of PPMV-1 was isolated from outbreaks in a vaccinated racing pigeon (Columbia livia) loft in China, namely, PPMV-1/pigeon/Gansu/China/02/2020 (GS02). Experimental infection with GS02 showed mortality rates of 100% and 87.50% in 4- and 12-week-old pigeons, respectively, suggesting that GS02 is virulent and more sensitive to young pigeons. The whole genome of GS02 determined the fusion (F) protein possessing virulence cleavage site 112RRQKRF117. Phylogenetic analysis indicated that GS02 was a subgenotype VI.2.1.1.2.2 (VIk) of Class II NDV and more closely related to the JS/06/20/Pi (MW271791) strain, but it was far from the genetic distance from the commercial vaccine chicken-origin La Sota strain. Using inactivated GS02 as a vaccine candidate and inactivated vaccine La Sota to immunize the pigeons, both of them provided complete protection against GS02 challenge. The GS02 vaccine candidate induced higher antibody titers than the La Sota vaccine, and cross-reactivity testing showed antigenically slight differences between GS02 and La Sota. These results indicated that the GS02 candidate could be a potential pigeon-derived vaccine for the prevention and control of PPMV-1 in pigeons.